Niche separation and weak interactions in the high tidal zone of saltmarsh‐mangrove mixing communities. Issue 9 (25th March 2021) - Ndayambaje, Patrick; Wei, Lili; Zhang, Tingfeng; Li, Yuhong; Liu, Lin; Huang, Xu; Liu, Chaoxiang
Abstract: Saltmarsh‐mangrove ecotones occur at the boundary of the natural geographic distribution of mangroves and salt marshes. Climate warming and species invasion can also drive the formation of saltmarsh‐mangrove mixing communities. How these coastal species live together in a "new" mixed community is important in predicting the dynamic of saltmarsh‐mangrove ecosystems as affected by ongoing climate change or human activities. To date, the understanding of species interactions has been rare on adult species in these ecotones. Two typical coastal wetlands were selected as cases to understand how mangrove and saltmarsh species living together in the ecotones. The leaves of seven species were sampled from these coastal wetlands based on their distribution patterns (living alone or coexisting) in the high tidal zone, and seven commonly used functional traits of these species were analyzed. We found niche separation between saltmarsh and mangrove species, which is probably due to the different adaptive strategies they adopted to deal with intertidal environments. Weak interactions between coexisting species were dominated in the high tidal zone of the two saltmarsh‐mangrove communities, which could be driven by both niche differentiation and neutral theory. Synthesis. Our field study implies a potential opportunity to establish a multispecies community in the high tidal zone of saltmarsh‐mangrove ecotones, where the sediment was characterized by low salinity and high nitrogen. Abstract : We found niche separation between saltmarsh and mangrove species and weak interaction between coexisting species in the high tidal zone of the saltmarsh‐mangrove mixing communities.